(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
This experiment goal was to identify the effect of parity and body condition score (BCS) on oestrus expressions (OE), post breeding reproductive performance (PBRP) of Katjang crossbred and changes of progesterone (P4) concentration. Twenty-four does were treated with 14 days synchronisation followed by visual observation of oestrus expressions (standing heat (SH), mounted by other buck but not standing (MBNS), vocalization (VC), tail swaging (TW), and sniffing of the genital of other buck (SGB)) and blood sampling twice daily up to 72 hours following Control Internal Drug Release (CIDR) removal. PBRP data was recorded for evaluation which included pregnancy rate (PR), abortion rate (AR), mortality rate (MR), litter size (LS), litter birth weight (LBW) and gestation length (GL). Result revealed that there was no significant effect (P>0.05) of parity and BCS on OE, PBRP and progesterone concentration except for birth weight which had been affected by parity. Based on observation of OE of SH, it was found that accuracy of pregnancy prediction was up to 50%. Analysis of OE established reliability of OE in was sequence from SH>SGB>TW>MBNS>VC and onset of oestrus began approximately 33h post to CIDR removal. Analysis of PBRP shown parity 2 had heavier birth weight in single litter size than parity 3 which was associated with no MR. Progesterone concentration indicated all of the does were on oestrus and highly susceptible as early as 48 h post to CIDR removal. In conclusion, this study demonstrated that both non-genetic factors; parity and BCS are very poor in determining the effect of OE, PBRP and P4 concentration due to limitation of sample size and greater influences of external factors such as weather, extreme environmental condition and farm management. It is recommended to improve program in future by focusing on enhancing the fertilization rate and reducing embryonic loss for optimum conception rate.